Is Sharia peer-to-peer lending in Indonesia accountable and transparent? - Indrarini, Rachma; Samsuri, Andriani; Syam, Nur; Room Fitrianto, Achmad; Zulfa, Indana (Universitas Negeri Surabaya, 2025)
Financial technology is developing in Indonesia, especially in peer-to-peer landing. Based on data from the Indonesia Authority of Financial Service (OJK), there are 102 peer-to-peer lending institutions in Indonesia with 8 of them using the Sharia system. Every Sharia-based transaction must ensure its accountability not only to the public but also to God. Accountability can be seen in the financial statements and annual reports were transparent and accountable. This study aims to see the transparency and accountability of peer-to-peer lending in Indonesia. This study used a qualitative phenomenological approach to observe the problem. The results showed that not all peer-to-peer lending sharia in Indonesia is transparent and accountable. Only three out of eight peer-to-peer landings are transparent and accountable.